Nierówności edukacyjne jako problem społeczny w społeczeństwach posttransformacyjnych - Długosz, Piotr (Wydawnictwo UJ, 2017)
The article presents results of the research on educational inequalities in Poland, Ukraine and Hungary. Th e research was conducted with the use of the survey method and the auditorium questionnaire technique. Th e research sample was chosen using the quota sampling method. Secondary school-leavers were the respondents. 1232 students were researched in Poland, 392 in Ukraine and 359 in Hungary. Th e results of the research have shown that educational inequalities perceived as a relation between socio-economic status and educational aspirations and school achievements are present in all the researched countries. Th e conducted analyses have shown that high educational aspirations and high school achievements are in correlation with higher status and cultural and economic capital as well as sex.
Educational inequalities as a social problem in post-transformational societies
Keywords: social problems; educational inequalities; educational aspirations; youth